Dispersion degree data and chemical properties of Nigerian steel bars used as structural element - Ehizemhen Igibah, Christopher; Omolayo Agashua, Lucia; Abubakar Sadiq, Adavudi (International Journal of Engineering and Technology, 2019)
The study was aimed at assessing degree of uncertainty, effect of water and other chemicals on both locally made and imported reinforcement used for structural elements via Optical Emission Spectrometry technique. Reinforcement from various locations in Lagos state, Nigeria was soaked with chemicals (NaOH, Na2SO4, H2SO4, HCl and H2O) to detect chemicals impact. The results indicated that Carbon, phosphorus and sulphur of Pulkit reinforcement was within ASTM limit. The severity of aqueous solutions on steel rebars was in the order H2SO4 > HCl > Na2SO4 > H2O for both local and imported local bars, while steel rebars were not affected by NaOH solution. Degree of dispersion (COV) of local steel was the highest. This was in terms of elongation of 23.69%, H2SO4 of 0.39% and 1.24% for one and six weeks respectively.Â